PENGARUH MODEL PEMBELAJARAN SAVI BERBANTUAN LAGU ANAK BERBAHASA INGGRIS UNTUK MENINGKATKAN KETERAMPILAN LISTENING SISWA KELAS IV SDN 060866 MEDAN TIMUR - Sardame Hotmauli Sitompul; Albert Pauli Sirait; Zainuddin; Eva Betty Simanjuntak; Tiarnita M.S Br Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model assisted by English children's songs on the listening skills of fourth-grade students at SDN 060866 Medan Timur. This study was motivated by the low listening skills of students due to the use of less varied learning models and media. The study used a quantitative approach with a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of 50 fourth-grade students consisting of an experimental class and a control class with a total sampling technique. Data were collected through listening skills tests and observations, then analyzed using descriptive statistics, prerequisite tests, Wilcoxon Signed-Rank Tests, and N-Gain analysis with the help of SPSS. The results showed that the implementation of the SAVI model ran very well through the involvement of students' somatic, auditory, visual, and intellectual activities. The improvement in listening skills in the experimental class was higher than in the control class. The results of the Wilcoxon test showed a significance value <0.001, so there was a significant effect of the application of the SAVI model assisted by English children's songs on students' listening skills. The N-Gain analysis yielded an average score of 0.4156, categorized as moderate. Therefore, the SAVI model, aided by English children's songs, is effective as an alternative learning method to improve elementary school students' listening skills.